2018
DOI: 10.18311/jbc/2017/16279
|View full text |Cite
|
Sign up to set email alerts
|

Biology and functional Response of Andrallus spinidens (F) to the rice army worm Spodoptera mauritia (Boisduval)

Abstract: ABSTRACT:The pentatomid bug, Andrallus spinidens (F.), is a polyphagous predator on lepidopteran larvae in rice fields in India. The basic biology and predatory potential of the bug was studied under laboratory conditions. The nymphs were reared in petri dishes and were fed 3 rd to 5 th instar Spodoptera mauritia (Boisduval) larvae. The mean development period from egg to adult was 21 days. Eggs were laid in batches of 45 to 95 and the mean total number of eggs laid by each female was 259. The second, third an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 3 publications
0
7
0
2
Order By: Relevance
“…1A). Each female may lay 2-6 patches containing 7-96 eggs (Rezvani and Shahosseini 1976;Shanker et al 2017) depending on host prey and climate both in the field and laboratory (Rezvani and Shahosseini 1976;Manley 1982;Singh and Singh 1989).…”
Section: Biologymentioning
confidence: 99%
See 2 more Smart Citations
“…1A). Each female may lay 2-6 patches containing 7-96 eggs (Rezvani and Shahosseini 1976;Shanker et al 2017) depending on host prey and climate both in the field and laboratory (Rezvani and Shahosseini 1976;Manley 1982;Singh and Singh 1989).…”
Section: Biologymentioning
confidence: 99%
“…The period of embryonic growth in A. spinidens has been reported as 7.63 days at 26.6°C (Rajendra and Patel 1971), 6.6 days under field conditions (Singh and Singh 1989), 9 days at 26.6°C (Javadi et al 2005), 6-10 days at 25°C (Shanker et al 2017) and 6.41-6.77 days at four locations of northwestern Himalayan regions (Bhojendra et al 2019). Shintani et al (2010) indicated the temperature of 16.5°C and 102.9 degree-days as the developmental zero and thermal constant of the eggs.…”
Section: Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Inside the container of paired adults some strips of blotting paper was provided as substrate for oviposition. After oviposition, egg batches were removed with paper strips and placed in separate plastic containers (20 × 20 × 15cm) to record incubation period and hatching per cent (Shanker et al, 2017;Tiwari et al, 2017). All experiments were performed with three replications for each location.…”
Section: Study On Variability In Biology Of Andrallus Spinidens Collected From Different Locationsmentioning
confidence: 99%
“…To study the variability in predatory efficiency of A. spinidens from different location, each nymphal instar reared on the larvae of Spodoptera litura was investigated. (Uematsu, 2006;Shanker et al, 2017).…”
Section: Study On Variability In Predatory Efficency Of Andrallus Spinidens From Different Locationmentioning
confidence: 99%